Prevalence of overweight and obesity among adolescents in South Indian population - Dr. Gayathri D.; Dr. Syamily; Dr. M. Kulandaivel (International Journal of Medical Research and Review, 2020)
Introduction: Childhood obesity is one of the global public health challenges of the 21st century, affecting every country in the world. Globally, in just 40 years the prevalence of obesity has raised more than 10-fold from 11 million to 124 million school-age children.Material and Methods: This study is a school-based cross-sectional study. The study population is 150 children from 11-14 years old school children from a selected private school in urban Pondicherry.Result: In the present study it was observed the prevalence of overweight and obesity shows that the prevalence of overweight is 18% (N=27) and Obesity is 6% (N=9) based on BMI. Overweight and Obesity is an emerging major health problem in school children in our Country.Conclusion: In the present study, there is an increase in the prevalence of overweight /obesity in school children.